Electron backscatter diffraction in the study of microdeformations in zircon grains from meteorite craters: methodological aspects - Davletshina, A. A.; Chebykin, N. S.; Zamyatin, D. A. (Litosfera (Ekaterinburg. Online), 2025)
Subject of Research.  Methodological aspects of sample preparation and electron backscatter diffraction (EBSD) in the study of microdeformations in zircon grains. Objects and Methods.  Fragments of impactites from shock-metamorphosed rocks of the Vredefort (South Africa) and Kara (Pay-Khoy Ridge, Yugorsky Peninsula, Russia) impact craters were investigated using scanning electron microscopy (SEM) and electron backscatter diffraction. Results.  The identification of zircon grains with specific microdeformations requires high-spatial-resolution (tens of nanometers) examination of large polished rock surfaces, which demands significant instrument time. To reliably detect microdeformations in zircon, the following methodological challenges were addressed: (1) analyzing the influence of Electron Backscatter Diffraction Pattern (EBSP) imaging conditions at different beam accelerating voltages (10, 20, and 29 kV) on the signal-to-noise ratio, spatial resolution, and Kikuchi band width; (2) comparing zircon grain orientation maps obtained at different voltages; (3) developing an algorithm for mineral identification and microdeformation finding; and (4) validating the methodology on zircon grains from the Vredefort and Kara impact craters. Conclusions.  The sample preparation methodology for EBSD analysis was refined, and methods for processing EBSD data to improve Kikuchi diffraction pattern indexing were explored. The efficiency of detecting and analyzing shock-metamorphosed zircon grains using scanning electron microscopy was enhanced through optimized electron imaging and EBSD mapping conditions. An algorithm for mineral identification in thin sections (rock slices) was developed. The methodology was validated on a series of 50 thin sections from the Kara and Vredefort impactites, resulting in the identification of 436 zircon grains, including all known types of zircon microdeformations.